2013
DOI: 10.1016/j.scitotenv.2012.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and respiratory symptoms among children with asthma: Vulnerability by corticosteroid use and residence area

Abstract: Rationale Information on how ambient air pollution affects susceptible populations is needed to ensure protective air quality standards. Objectives To estimate the effect of community-level ambient particulate matter (PM) and ozone (O3) on respiratory symptoms among primarily African-American and Latino, lower-income asthmatic children living in Detroit, Michigan and to evaluate factors associated with heterogeneity in observed health effects. Methods A cohort of 298 children with asthma was studied prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
1
30
1
1
Order By: Relevance
“…We found statistically significant increases for occurrence of at least one symptom, cough and phlegm. Our results are consistent with previous studies showing an increase in asthma symptoms for urban areas, (Yu et al, 2000;Escamilla-Nunez et al, 2008;Lewis et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…We found statistically significant increases for occurrence of at least one symptom, cough and phlegm. Our results are consistent with previous studies showing an increase in asthma symptoms for urban areas, (Yu et al, 2000;Escamilla-Nunez et al, 2008;Lewis et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…123,124 Patients with severe asthma might be the most likely to have respiratory symptoms with exposure to air pollutants, despite treatment with steroids. 125 Because of the potential interactive effects of air pollutants with allergens or secondhand smoke, avoidance of these exposures is prudent, especially during high pollution days, which may be concurrent with exposure to seasonal aeroallergens.…”
Section: Discussionmentioning
confidence: 99%
“…Lippmann et al found that spatial inhomogeneity of air pollutant concentrations may hide negative associations with human health (Lippmann et al, 2000). Generally, odds for respiratory symptoms may be increased by O 3 exposure but result in application of appropriate medicaments and not hospitalization (Altug et al, 2014; Lewis et al, 2013). Therefore, we assume that unidentified factors and/or the negative correlation between concentrations of O 3 and the other investigated pollutants may mask rather small adverse health effects of ozone.…”
Section: Ozonementioning
confidence: 98%